Simbol, Makna, dan Solidaritas: Strategi Digital Komunitas Urban di Indonesia dalam Membangun Eksistensi di Instagram - Firsanty, Farah Putri; Amanatin, Elsa Lutmilarita; Adiansah, Wandi (Sociology Department Of Syiah Kuala University, 2025)
Digitalization has spurred the emergence of diverse online communities in urban spaces, however, the dynamics of their existence and sustainability remain underexplored. This study aims to address the question: How are the dynamics of the existence of online communities in Indonesia formed and sustained through digital practices? To answer this, a qualitative approach is employed using netnography, a method specifically designed to observe community practices within digital environments. The research involves observations of six Instagram accounts belonging to social communities actively engaged in poverty alleviation issues: @mataharikecil_id, @satoeatap, @sschildsurabaya, @kpajmakassar, @rmhpelangi, and @ytsb_official.The findings reveal that social media, particularly Instagram, plays a significant role in establishing community presence while also attracting public participation through donations and volunteer recruitment. These communities utilize Instagram as a space for symbolic interaction, crafting a credible and emotionally resonant image that fosters public trust. This image is constructed through a combination of visual content, persuasive narratives, informational transparency, and active engagement with audiences. Through these strategies, the communities are able to forge strong digital social relations and expand their networks of solidarity. This study demonstrates that the presence of digital communities is not solely determined by their online visibility, but also by their ability to construct shared meanings with the public as participatory actors.AbstrakDigitalisasi telah mendorong munculnya beragam komunitas online di ruang-ruang urban, namun dinamika eksistensi dan keberlanjutannya masih jarang dikaji secara mendalam. Penelitian ini bertujuan menjawab pertanyaan: bagaimana dinamika eksistensi komunitas online di Indonesia terbentuk dan dipertahankan melalui praktik digital? Untuk itu, studi ini menggunakan pendekatan kualitatif melalui metode netnografi, yang secara khusus diarahkan untuk mengamati praktik komunitas dalam ruang digital. Observasi dilakukan terhadap enam akun Instagram komunitas sosial yang aktif di isu pengentasan kemiskinan: @mataharikecil_id, @satoeatap, @sschildsurabaya, @kpajmakassar, @rmhpelangi, dan @ytsb_official. Temuan menunjukkan bahwa media sosial, khususnya Instagram berperan signifikan dalam membangun eksistensi komunitas sekaligus menarik partisipasi publik, baik melalui donasi maupun rekrutmen relawan. Komunitas memanfaatkan Instagram sebagai ruang interaksi simbolik untuk membentuk citra yang kredibel dan menyentuh secara emosional, yang pada gilirannya menumbuhkan kepercayaan publik. Citra tersebut dibangun melalui kombinasi konten visual, narasi ajakan, transparansi informasi, serta interaksi aktif dengan audiens. Melalui strategi ini, komunitas mampu menciptakan relasi sosial digital yang kuat dan memperluas jaringan solidaritas. Studi ini memperlihatkan bahwa keberadaan komunitas digital tidak hanya ditentukan oleh kehadiran daring, tetapi juga oleh kemampuan mereka dalam membangun makna bersama dengan publik sebagai aktor partisipatif.